2023
DOI: 10.3390/metabo13040564
|View full text |Cite
|
Sign up to set email alerts
|

Is the Novel Slot Blot a Useful Method for Quantification of Intracellular Advanced Glycation End-Products?

Abstract: Various types of advanced glycation end-products (AGEs) have been identified and studied. I have reported a novel slot blot analysis to quantify two types of AGEs, glyceraldehyde-derived AGEs, also called toxic AGEs (TAGE), and 1,5-anhydro-D-fructose AGEs. The traditional slot blot method has been used for the detection and quantification of RNA, DNA, and proteins since around 1980 and is one of the more commonly used analog technologies to date. However, the novel slot blot analysis has been used to quantify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 109 publications
0
23
0
Order By: Relevance
“…Kehm et al measured arg-pyrimidine- and pentosidine-positive areas in the pancreatic islets (AGEs area/pancreatic islets) [ 11 ], while van Heijist et al revealed that heat shock protein (HSP) 27 and arg-pyrimidine were co-located in the immunostaining images of squamous cell carcinoma tissue in patients with non-small cell lung cancer; arg-pyrimidine-modified HSP27 was also located in this tissue [ 46 ]. Considering the characteristics that require anti-AGE antibodies, immunostaining [ 2 , 11 , 12 , 46 ], Western blotting [ 2 , 13 , 32 ], slot blotting [ 2 , 14 , 15 , 16 ], and ELISA [ 10 , 17 , 18 ] can be grouped together. Moreover, if the structure of AGEs remains unclear (e.g., AGEs with an unknown structure generated from methylglyoxal and bovine serum albumin [BSA] [ 47 ]), it can still be examined using anti-AGE antibodies produced against the AGEs for the antigen.…”
Section: Techniques For Analyzing Agesmentioning
confidence: 99%
See 4 more Smart Citations
“…Kehm et al measured arg-pyrimidine- and pentosidine-positive areas in the pancreatic islets (AGEs area/pancreatic islets) [ 11 ], while van Heijist et al revealed that heat shock protein (HSP) 27 and arg-pyrimidine were co-located in the immunostaining images of squamous cell carcinoma tissue in patients with non-small cell lung cancer; arg-pyrimidine-modified HSP27 was also located in this tissue [ 46 ]. Considering the characteristics that require anti-AGE antibodies, immunostaining [ 2 , 11 , 12 , 46 ], Western blotting [ 2 , 13 , 32 ], slot blotting [ 2 , 14 , 15 , 16 ], and ELISA [ 10 , 17 , 18 ] can be grouped together. Moreover, if the structure of AGEs remains unclear (e.g., AGEs with an unknown structure generated from methylglyoxal and bovine serum albumin [BSA] [ 47 ]), it can still be examined using anti-AGE antibodies produced against the AGEs for the antigen.…”
Section: Techniques For Analyzing Agesmentioning
confidence: 99%
“…Slot blot analysis is generally performed to quantify AGEs [ 2 , 14 , 15 , 16 ]. In 2017, we developed a novel slot-blot method with the following characteristics: (i) a lysis buffer containing tris-(hydroxymethyl)-aminomethane (Tris), urea, thiourea, and 3-[3-(cholamidopropyl)-dimethylammonio]-1-propanesulfonate (CHAPS), and (ii) polyvinylidene fluoride (PVDF) membranes [ 2 ].…”
Section: Techniques For Analyzing Agesmentioning
confidence: 99%
See 3 more Smart Citations